Hubungan antara Self Efficacy dan Self Care Behavior pada Lansia dengan Hipertensi - Wimar Anugrah Romadhon; Joni Haryanto; Makhfudli Makhfudli; Setho Hadisuyatmana (FORIKES, 2020)
Background: The incidence of hypertension in the elderly continues to increase every year and the problems that often occur in elderly hypertension are non-compliance with therapy or treatment, lifestyle changes, self care behavior that is less than optimal and the complications due to hypertension. This is influenced by beliefs (self-efficacy) that the elderly have to change their behavior, which is self care behavior which is not good. Purpose: to observe the relationship between self efficacy and self care behavior in the elderly with hypertension. Method: This study used a descriptive correlation design with a cross sectional approach. Overall, the samples obtained were 252 elderly with hypertension in the Surabaya Public Health Center area through cluster random sampling. Data were analyzed using the Spearman Rank test. Results: The elderly with hypertension have a self efficacy of 40.9% in the low category and 59.1% in the good category and have a self care behavior of 31.7% in the less category, 39.3% in category enough, 29% in the good category. This study shows a significant relationship between self efficacy and self care behavior with a value of p = 0,000